2017
DOI: 10.7575/aiac.ijalel.v.6n.4p.21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Explicit Instruction of Formulaic Sequences in Pre-Writing Vocabulary Activities on Foreign Language Writing

Abstract: The present study investigates the effect of the explicit instruction of formulaic sequences in pre-writing vocabulary activities on foreign language writing. To this end, a total of 81 Saudi pre-intermediate learners of English as a foreign language participated in a 10-week study of a pretest/posttest design. In every 2-hour session of a total of 10 sessions, the participants were required to read a news story and then re-write it individually without looking back at the original story. During the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…The results of the study revealed that the instruction of lexical bundles significantly develops Turkish prospective EFL teachers' writing skills in terms of accuracy and appropriacy. The findings of the present study were aligned with the literature (Kazemi et al, 2014;AlHassan & Wood, 2015;Latifi & Afraz, 2015;El-Dakhs et al, 2017;Nemati, 2019;Kanglong & Afzaal, 2020;Yilmaz & Koc, 2020;Birhan, 2021) that concluded that explicit instruction of lexical bundles significantly affected the writing abilities of learners.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the study revealed that the instruction of lexical bundles significantly develops Turkish prospective EFL teachers' writing skills in terms of accuracy and appropriacy. The findings of the present study were aligned with the literature (Kazemi et al, 2014;AlHassan & Wood, 2015;Latifi & Afraz, 2015;El-Dakhs et al, 2017;Nemati, 2019;Kanglong & Afzaal, 2020;Yilmaz & Koc, 2020;Birhan, 2021) that concluded that explicit instruction of lexical bundles significantly affected the writing abilities of learners.…”
Section: Discussionsupporting
confidence: 91%
“…The necessity of an extended practice time to maintain the acquisition of the targeted lexical bundles was also pinpointed by Al-Hassan andWood (2015), andEl-Dakhs, Prue, andIjaz (2017). According to them, a prolonged practicing time did not only help participants acquire and internalize the new multi-word units, but it also led to the comprehension of their structures and usage, and enabled learners to correctly implement them in writing.…”
Section: Discussionmentioning
confidence: 99%